2022
DOI: 10.1007/s10452-021-09928-4
|View full text |Cite
|
Sign up to set email alerts
|

Fishermen’s knowledge and conservation attitudes: focus on the great cormorant Phalacrocorax carbo (Linnaeus, 1758) in the Minho River, Portugal

Abstract: Considerate the attitudes of traditional communities and their local ecological knowledge (LEK) can contribute to better policymaking and more appropriate management plans. Thus, this study strived to share the Minho River’s fishermen LEK about great cormorant Phalacrocorax carbo (Linnaeus, 1758), as well as it exposes their conservation attitudes towards this species. We described and analysed interviewees’ LEK qualitatively, while their attitudes were analysed quantitatively through co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…This value is lower than among fishermen in Portugal in 2022. 16 The results of the different fish grills are presented in Figure 17b and they indicated that 64.91% (n = 37) of participants chose to grill as a method of cooking fish, 24.56% (n = 14) 90.0 0% of participants stated that scrambling was the best way to cook a fish, and only 10.53% (n = 6) of participants preferred fried fish. Regarding the seasons, 92.98% (n = 53) of the participants stated that all seasons were preferred for fish consumption, while 7.02% (n = 4) of the participants eat fish only in the summer and spring seasons.…”
Section: B) Responses By the Fishermen Socio-demographic Status Of Pa...mentioning
confidence: 99%
“…This value is lower than among fishermen in Portugal in 2022. 16 The results of the different fish grills are presented in Figure 17b and they indicated that 64.91% (n = 37) of participants chose to grill as a method of cooking fish, 24.56% (n = 14) 90.0 0% of participants stated that scrambling was the best way to cook a fish, and only 10.53% (n = 6) of participants preferred fried fish. Regarding the seasons, 92.98% (n = 53) of the participants stated that all seasons were preferred for fish consumption, while 7.02% (n = 4) of the participants eat fish only in the summer and spring seasons.…”
Section: B) Responses By the Fishermen Socio-demographic Status Of Pa...mentioning
confidence: 99%